The physics of high brightness beams : proceedings of the 2nd ICFA Advanced Accelerator Workshop - Rosenzweig, J. (Jamie); Serafini, Luca (World Scientific, 2000)
This book contains the proceedings of the 1999 ICFA workshop on the physics of high brightness beams. The workshop took a snapshot in time of a fast moving, interdisciplinary field driven by advanced applications such as high gradient, high energy physics linear colliders, high gain free electron lasers, heavy ion fusion, and transmutation of nuclear materials. While the field of high brightness beam physics has traditionally been divided into disparate electron and heavy ion communities, the workshop brought the two types of researchers together, so that a sharing of insights and methods could be achieved. Thus, this book represents a unifying step in the development of the diverse fascinating discipline of high brightness beam physics, with its challenges rooted in collective, nonlinear particle motion and ultra-high electromagnetic energy density.